Working towards enhancing the quality of urban life through a greener city: aspects of policy and law in Malaysia relevant to urban green spaces development and environmental quality protection - Mustafa, Maizatun (The International Academic Forum, 2011)
Over the past decade, Malaysia has experienced a trend of rapid urbanization, with urban populations already represent over 60 percent of the total population. While urbanization is a natural consequence of economic development and industrialization, it does however lead to many challenges. One of which is the increasingly serious environmental pollution affecting the cities’ sustainable development goals including that of pursuing a higher quality of life for the people. Considering the importance of upholding this sustainability goal, Malaysia is identifying various issues for consideration and measures for implementation. To that end, it is recognizing the importance of urban forests in improving environmental quality, and in providing livable places for its urban residents. At the same time, it is also recognizing urban development as a major threat to forest and other green spaces within the cities. For these reasons, Malaysia’s policies on urban forest must take into account the need to promote tree-based resources catering to multiple urban demands, while balancing these demands against economic and other needs. For Malaysia, the implementation such forest policies has to be done through various means, including that of its integration within the legal framework. At present, there already exist a number of legislations that are directly or indirectly applicable to urban forests. In this paper, both these policies and laws are examined. The objective of this examination is to identify Malaysia’s direction towards developing and protecting forests and other green spaces within the urban areas for the benefit of urban population and sustainable development.